Micro-finance and women empowerment - Malleswari, B, 1980- (New Delhi : Serials Publications, 2010)
Study conducted in the state of Andhra Pradesh, India.
Originally presented as the author's thesis (Ph. D.)--Sri Venkateswara University, 2010.
Includes bibliographical references p. [244]-252.
Keywords: Microfinance -- India -- Andhra Pradesh